Item condition of the autonomic nervous system in patients with hypertension stage II low additional cardiovascular risk depending on the status of smokers - E. A. Poznanskaya; V. V. Syvolap (Zaporožskij Medicinskij Žurnal)
Beckground. This century is characterized by steady growth in the number of patients who have cardiac pathology combined with other factors, aggravating the disease and prognosis. High prevalence of smoking among young patients with hypertension. Research devoted to the study of influence of risk factors , including smoking, on the structural and geometric and functional changes of the heart is not enough.